Analysis of statistic health care as indicators of efficiency service in Semen Padang Hospital through Barber Johnson graph - Nasution, Nurhasanah (International Journal Of Community Medicine And Public Health, 2020)
Background: The efficiency of service delivery is very important for hospitals. One measurement of service indicators that can be used is the Barber Johnson graph (GBJ). GBJ is needed to see and measure the level of service efficiency in hospitals. The indicators used are bed occupancy rate (BOR), bed turnover rate (BTR), turnover interval (TI), and length of stay (LOS). This graph can also be used to compare or view hospital developments at different times, and to increase the likelihood of changes in one variable by changing other variables. This research was conducted at Semen Padang Hospital (SPH), Padang, West Sumatera, Indonesia. Methods: The purpose of this study was to determine the statistical value of hospital and hospital service efficiency levels by using the Barber Johnson graphic. This research method is descriptive by direct observation of the medical record file of inpatients since the January to December 2017 period. Results: Statistical data obtained from SPH in 2018 showed the value of service days 30132, and the Number of beds 144 units. From the data processing results obtained a total bed occupancy rate 60.83%, bed turnover rate 6.86 times, turnover interval 2 days and average length of stay 3 days. Conclusions: Statistical data obtained from SPH in 2018 shows the value of BOR, TI is in an efficient, while BTR and LOS are inefficient.